Extended therapeutic window for post-exposure treatment of ricin intoxication conferred by the use of high-affinity antibodies. (1st March 2017) - Noy-Porat, Tal; Alcalay, Ron; Epstein, Eyal; Sabo, Tamar; Kronman, Chanoch; Mazor, Ohad
Abstract: The plant toxin ricin is considered a potential bioterror agent against which there is no available antidote. To date, neutralizing antibodies are the most promising post-exposure treatment for ricin intoxication, yet so far they were shown to be effective only when given within several hours post exposure. As part of an ongoing effort to develop efficient ricin-countermeasures, we tested whether high-affinity antibodies that were previously isolated from immunized non-human primates, may confer effective post-exposure therapy for ricin-intoxicated mice treated at late time-points after exposure. While each antibody is capable of providing high protection rate by itself, a formulation consisting of three neutralizing antibodies that target different epitopes was tested to provide therapeutic coverage against different variants of the malicious pathogen. Indeed, the tri-antibody based cocktail was highly effective, its administration resulting in very high survival rates (>70%) when animals were treated as late as 48 h post exposure and significant protection (>30%) even at 72 h. This study establishes for the first time that anti-ricin antibodies can serve as a highly effective antidote at such late time-points after exposure. From the clinical point of view, the extended therapeutic window documented here is of high importance allowing adequate time to accurately identify the causative agent and may permit initiation of life-saving treatment with these antibodies even after the onset of clinical signs. Highlights: Ricin is a potential bioterror agent against which there is no available antidote. A tri-antibody based cocktail conferred very high survival rates when administered 48 h post exposure. The tri-antibody cocktail is a very promising candidate for clinical application as a passive vaccine for ricin.